Performance of Bread Wheat (Triticum aestivum L.) Varieties under Rainfed Condition of Sulaimani - Ali1, Sarkawt Hama Salih; Ahmad, Nariman Salih; Ahmad, Maki Mohammed; Ahmad, Dastan Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2018)
A study was conducted to investigate the performance of seven wheat varieties under rainfed conditions of Sulaimani. The varieties were sown in the field using CRBD with three replications. ANOVA revealed highly significant (p≤0.01) differences in almost parameters in different wheat varieties. Both principal component analysis and the cluster analysis revealed the presence of highly significant differences among the varieties for the studied characteristics. The local varieties had surpassed almost newly introduced genotypes for the yield and its components. Sham6 found to perform the maximum grain yield, followed by Barcelona variety. While for the same traits Ritraw and Mariboss had the least value. It is realized that the local genotypes are able to offer a reasonable yield even when the climatic condition does not allow for early sowing. While the other introduced varieties would offer the higher yield, by extending the growing period to express their genetic potential, if early sowing allowed. The variation investigated here implying high genetic potential of these genotypes in the future breeding program.
Keywords: Bread wheat; Rainfed Condition; Agronomical characteristics; Cluster analysis; Yield; and yield components